Equine Umbilical Cord Serum Composition and Its Healing Effects in Equine Corneal Ulceration - Peyrecave-Capo, Xavier; Saulnier, Nathalie; Maddens, Stéphane; Gremillet, Bérengère; Desjardins, Isabelle (Frontiers in Veterinary Science, 2022)
Background Human autologous serum (AS) and umbilical cord serum (UCS) both contain growth and neurotrophic factors that promote corneal healing. Aim Our objectives were to compare equine AS and UCS cytokine and growth factor profiles and to assess the safety and clinical feasibility of the therapeutic use of UCS eye drops in cases of spontaneous complex ulcers. Study Design Prospective clinical trial. Methods Vitamin A insulin growth factor, platelet-derived growth factor-BB, transforming growth factor (TGF)-β1 (enzyme-linked immunosorbent assay), interleukin (IL)-1β, IL-6, interferon-γ, and monocyte chemoattractant protein 1 concentrations were determined in 10 AS collected from different horses and 10 UCS sampled at delivery. Six client-owned horses presenting with complex non-healing corneal defects of >5 mm2 were included in a clinical trial and treated with conventional therapy and conditioned UCS drops for 8–15 days. Ulcer surface and time to complete epithelialization were recorded. Results Median concentrations of vitamin A, insulin growth factor, and platelet-derived growth factor-BB were not significantly different in AS compared with UCS (respectively, 14.5 vs. 12.05 μg/ml; 107.8 vs. 107.3 pg/ml; and 369.1 vs. 924.2 pg/ml). TGF-β1 median concentration in UCS was significantly higher than in AS (3,245 vs. 2571pg/ml) (p = 0.04). IL-1β, IL-6, interferon-γ, and monocyte chemoattractant protein 1 concentrations were variable in AS and undetectable in UCS. The corneal median ulcerative area was 37.2 mm2 (6.28–57.14 mm2) and had a duration of 4–186 days (median 19 days). All lesions healed within 13–42 days (median 17 days). No adverse effects nor recurrences within 1 month were noticed. Limitations The sample size was small. Spontaneous corneal epithelial defects presented with variable clinical characteristics. There were no age-matched control horses to assess corneal healing time and rate. Conclusion and Clinical Significance Equine UCS may be beneficial, as it contains no pro-inflammatory cytokines and a greater concentration of TGF-β1 compared with AS. Topical UCS appears safe and may potentially be used as adjunctive therapy for equine complex non-healing ulcers.